Dapsone – Reinventing the wheel or rekindling possibilities? - Ramesha M Bhat; Monisha Madhumita; Rochelle Cheryl Monteiro (Clinical Dermatology Review, 2024)
Dapsone, once a fabric dye, is a versatile pharmaceutical for treating diseases like leprosy, malaria, and HIV-AIDS-related pneumonia. Discovered in 1908 but not utilized for its antimicrobial properties until the 1930s, dapsone faced initial setbacks due to toxicity, prompting the development of a safer derivative, Promin. Chemically, dapsone's lipid-soluble nature allows for extensive distribution throughout the body and involves complex metabolism, with a variable elimination half-life. Its clinical efficacy is due to its bacteriostatic action, inhibiting dihydrofolic acid synthesis, and its anti-inflammatory effects on neutrophils. Dapsone's dosing is tailored to the individual's condition and is approved for various dermatological conditions. However, its use is limited by contraindications in certain anemic conditions and potential side effects such as hemolytic anemia and methemoglobinemia, necessitating careful monitoring and management strategies to mitigate risks. Despite these challenges, dapsone's broad therapeutic utility and ongoing research into its mechanisms maintain its status as a significant medical therapy.